THE EXPERIENCES FELT LIKE MEDIATORS BETWEEN CONSUMER PERCEPTION AND HALAL PRODUCT PURCHASE DECISIONS - Pratiwi, Dhita; Kara, Muslimin; K, Amiruddin; Masse, Rahman Ambo; Wahab, Abdul (Yayasan Education and Social Center, 2024)
This study investigates the function of purchasing experience as a mediator in the correlation between consumer perception and purchasing decisions regarding halal products in Indonesia. This research employs a quantitative methodology utilizing a survey approach, incorporating a questionnaire that addresses demographic factors, consumer perceptions, purchasing experiences, and purchasing decisions. The study engaged 400 respondents selected through stratified random sampling. The regression analysis results showed that consumer perception has a positive and significant influence on buying decisions of halal products (coefficient = 0.45, p <0.001). Furthermore, path analysis revealed that purchasing experience is a considerable mediator (mediation coefficient = 0.105, p <0.001), strengthening the relationship between consumer perception and purchasing decisions. A substantial part of the decision-making process is the purchasing experience, which encompasses both the quality of the service and the level of satisfaction it provides. By using bootstrapping to test the hypothesis, it was determined that the purchasing experience had a significant mediating effect on the relationship. The confidence interval for this finding was between 0.080 and 0.135, which indicates that the hypothesis was supported. These findings highlight the importance of providing customers with a pleasant shopping experience, which highlights the need to improve purchasing decisions for halal products